Identity Work, Humour and Disciplinary Power - Huber, Guy; Brown, Andrew D. (Organization studies, 2017)
How are people’s identities disciplined by their talk about humour? Based on an ethnographic study of a New York food co-operative, we show how members’ talk about appropriate and inappropriate uses of humour disciplined their identity work. The principal contribution we make is twofold. First, we show that in their talk about humour people engaged in three types of identity work: homogenizing, differentiating and personalizing. These were associated with five practices of talk which constructed co-op members as strong organizational identifiers, respectful towards others, flexible rule followers, not ‘too’ serious or self-righteous, and as autonomous individuals. Second, we analyse how this identity work (re)produced norms regulating the use of humour to fabricate conformist selves. Control, we argue, is not simply a matter of managers or other elites seeking to tighten the iron cage through corporate colonization to manufacture consent; rather, all organizational members are complicit in defining discourses, subject positions and appropriate conduct through discursive processes that are distributed and self-regulatory.